3-PG model enhancement by modifying soil water availability in a tropical Eucalyptus urophylla plantation - de Lemos, Cristiane Zani; Carrero, Omar; Hakamada, Rodrigo; Silva, Luis Fernando; Ferreira, Karina; Stape, José Luiz [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2023)
3-PG is a widely process-based model used to estimate forest growth. After 20 years of use, along with progress in scientific knowledge, some model processes can be improved, such as soil water balance. The objective of this study was to assess the enhancements in the 3-PG model for Eucalyptus urophylla by changing the soil water availability, which considers the depth of the root system in the soil profile as stand ages. To set up the model and assess the improvement, a site in Sao Paulo state, Brazil, was used. From this trial two treatments were selected: 1) control (operational fertilization, without irrigation) and 2) fertilized and irrigated. The model enhancement for rooting depth and the maximum amount of water available was based on a measured relationship between the above-ground height and below-ground root depth, by replacing the constant value of the available soil water in the original 3-PG with a dynamic amount that increases as the root system grows. This modification increased the model efficiency to estimate the stem biomass and the leaf area index. This work can be used by researchers and forest managers using the 3PG model, as there was a significant improvement in stem biomass estimates, where the root mean square error (RMSE) decreased from 18.22 (original) to 12.16 (increased) Mg ha-1 yr-1 for non-irrigated treatment, increasing the model accuracy in forest biomass estimates.
Aprimoramento do modelo 3-PG pela modificação da disponibilidade de água no solo em Eucalyptus urophylla
Keywords: Eco-physiological modeling; Forest growth; Forest modelling; Process-based modelling